Coastal Community Empowerment Model: The Role of Women during the Fish “Off-Season” in Building Family Food Security - Eny Haryati; Heny Widyawati Saptosari; Fedianty Augustinah (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
During the fishing off-season, fishers face difficulties going to sea, causing household income to decline while daily food needs remain. Coastal women often become the main economic support, yet their role has rarely been developed into an empowerment model. This study aims to develop a coastal-community empowerment model based on women’s roles in strengthening family food security during the off-season. A qualitative case-study design was conducted in a fishing community in Sumenep Regency, East Java. Twelve informants were purposively selected, consisting of eight women from fishing families as key informants and four supporting informants. Data were collected through in-depth interviews, direct observation, and document tracing, then analysed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, with triangulation used to ensure validity. The findings show that women contribute to all four pillars of food security: availability, access, utilisation, and stability, while serving as the main economic buffer when husbands cannot fish. However, their efforts remain largely survival-oriented and are constrained by limited capital, narrow market access, and double workloads. The study concludes that an off-season-adaptive women’s empowerment model aligned with the seasonal calendar is needed to support more independent and sustainable livelihoods.